Clinical Correlates of Moderate-to-Severe Bronchopulmonary Dysplasia in Preterm Infants following Surgical Necrotizing Enterocolitis - Garg, Parvesh M.; Pippin, Melissa; Zhang, Mengna; Ware, Jennifer; Nelin, Sarah; Paschal, Jaslyn; Varshney, Neha; Hillegass, William B. (American Journal of Perinatology, 2022)
Objective The aim of the study is to determine clinical correlates of moderate to severe bronchopulmonary dysplasia (BPD) in preterm infants following surgical necrotizing enterocolitis (NEC).Study Design This is a retrospective, single-center cohort study comparing patients with moderate to severe BPD to patients with non/mild BPD among surgical NEC infants. BPD was defined by NIH 2001 consensus definition.Results Of 92 consecutive neonates with surgical NEC, 77% (71/92) had moderate/severe BPD and 22% (21/92) had non/mild BPD. The patent ductus arteriosus (PDA) was significantly higher in those developing moderate/severe BPD (67.6% [48/71]) than non/mild BPD (28.6% [6/21]; p = 0.001). Postoperatively, infants with moderate/severe BPD had more severe acute kidney injury (AKI; 67.6 [48/71] vs. 28.6% [6/21]; p = 0.001), were intubated longer (40.5 [interquartile (IQR): 12, 59] vs. 6 days [IQR: 2, 13]; p <0.001), received more parenteral nutrition (109 [IQR: 77, 147] vs. 55 days [IQR: 19, 70]; p <0.001), developed higher surgical morbidity (46.5 [33/71] vs. 14.3% [3/21]; p = 0.008), had more intestinal failure (62.5 vs. 13.3%; p <0.001), required a longer hospital stay (161 [IQR: 112, 186] vs. 64 days [IQR: 20, 91]; p <0.001), and were more likely to need home oxygen. In a multivariable analysis, lower birth weight (OR = 0.3, [95% confidence interval (CI): 0.1–0.5]; p = 0.001), PDA (OR = 10.3, [95% CI: 1.6–65.4]; p = 0.014), and longer parenteral nutritional days (OR = 8.8; [95% CI: 2.0–43.0]; p = 0.005) were significantly and independently associated with higher odds of moderate/severe versus non-/mild BPD.Conclusion Development of moderate/severe BPD occurred in the majority of preterm infants with surgical NEC in this consecutive series. Preterm infants with moderate/severe BPD were more likely to have a PDA before NEC. Development of moderate/severe BPD was associated with significantly greater burden and duration of postoperative morbidity following surgical NEC. Identifying surgical NEC infants at increased risk of moderate/severe BPD and developing lung protection strategies may improve surgical NEC outcomes.Key Points
Keywords: necrotizing enterocolitis; preterm Infants; BPD